A Study of Sleep Habits of the Students of Primary Schools of Rasht City From ‎Parents, Point of View - mehri yuosefgomrokchi; zahra shafi poor; ezat paryad; zahra atarkarruoshan (Guilan University of Medical Sciences, 2009)
Introduction: Sleep and enough rest are the primary requirements of human, s health and survival ‎and the quality of sleep has a significant role in improving and maintaining health. Sleep habits are ‎effective on the quality and quantity of sleep during childhood.‎ Objective: This study is carried out to identify the sleep habits of the students of primary schools. ‎ Methods: This is a cross – sectional study. The research society included all school age children in ‎the age range of ‎‏7‏‎ to ‎‏11‏‎, studying in districts ‎‏1‏‎ and ‎‏2‏‎ of Rasht city. Among these, ‎‏768‏‎ boy and girl ‎students of primary schools were selected from both districts using cluster method. Data gathering ‎tool was a questionnaire including two parts. The first part acquires personal and family information ‎and the second part includes ordinary questions about sleep, answered by the mothers. To analyze ‎the data, inferential and descriptive statistical methods were used.‎ Results: The research findings reveal that night – long insomnia is the most prevalent sleep habits ‎with the point of ‎‏1.79‏‎ ± ‎‏0.43‏‎ and ‎‏94.7%‏‎ always wake up during the night with perspiration and ‎scream and they do not become calm easily. These are the most prevalent sleep behavior in children ‎under study. There was also significant relation between the sleep habits of the children with their ‎age, educational grade, sharing bedroom with a brother or sister, participating in sport classes, ‎numbers of children in family, numbers of family members, parents, educational level, parents, ‎occupation, and monthly income(P<‎‏0.01‏‎).‎ Conclusion: In consideration of the mean value and the general standard deviation calculated(‎‏1.55‏‎ ‎‎± ‎‏0.17‏‎) which is higher than the scale mean(‎‏1.5‏‎) and since high mean value implies improper sleep ‎habits, it can be deducted that the sleep habits of children residing in Rasht is not proper.‎